2013
DOI: 10.1007/s10951-013-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Review of real-time vehicle schedule recovery methods in transportation services

Abstract: This paper presents a comprehensive review on methods for real-time schedule recovery in transportation services. The survey concentrates on published research on recovery of planned schedules in the occurrence of one or several severe disruptions such as vehicle breakdowns, accidents, and delays. Only vehicle assignment and rescheduling are reviewed; crew scheduling and passenger logistics problems during disruptions are not. Real-time vehicle schedule recovery problems (RTVSRP) are classified into three clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 90 publications
(140 reference statements)
0
20
0
Order By: Relevance
“…In this section, we present the related studies in the literature on the MDVSP and disruption management. We refer the interested reader to Visentini et al (2014) for an extensive review on various recovery methods. Although most of the solution methodologies are heuristics and handle the disruptions at the operational level, there exist few studies proposing exact approaches that incorporate robustness in their model in the planning stage.…”
Section: Related Literaturementioning
confidence: 99%
“…In this section, we present the related studies in the literature on the MDVSP and disruption management. We refer the interested reader to Visentini et al (2014) for an extensive review on various recovery methods. Although most of the solution methodologies are heuristics and handle the disruptions at the operational level, there exist few studies proposing exact approaches that incorporate robustness in their model in the planning stage.…”
Section: Related Literaturementioning
confidence: 99%
“…Optimization algorithms for planning transportation services according to [18,19] generally fall into several broad categories: (i) vehicle assignment and rescheduling; (ii) crew scheduling; and (iii) passenger logistics. Many of these processes rely on the generation of a schedule prior to use, but with sufficient vehicle and station instrumentation, efficient real-time scheduling and dispatch for vehicles in an optimal manner are achievable.…”
Section: Related Workmentioning
confidence: 99%
“…The vast majority of infrastructure-related work is focused on urban intersection handling where wireless vehicle-to-infrastructure (V2I) communication is in vehicle right-of-way coordination [12,13]. Lastly, high-level strategies for improving traffic flow generally focus on headway regulation [14,15] and optimal routing [16,17].Optimization algorithms for planning transportation services according to [18,19] generally fall into several broad categories: (i) vehicle assignment and rescheduling; (ii) crew scheduling; and (iii) passenger logistics. Many of these processes rely on the generation of a schedule prior to use, but with sufficient vehicle and station instrumentation, efficient real-time scheduling and dispatch for vehicles in an optimal manner are achievable.…”
mentioning
confidence: 99%
“…Since the 1990s, most research has focused on the VSP with multiple depots (MDVSP) (Kliewer et al, 2006), which is proven to be NP-hard by Bertossi et al (1987). Meanwhile, more realistic characteristics have been included, such as fuel consumption (Haghani and Banihashemi, 2002;Li, 2014), time windows (Desaulniers et al, 1998;Kliewer et al, 2011), multiple vehicle types (Kliewer et al, 2006;Ceder, 2011;Hassold and Ceder, 2014), integration with timetabling (Ibarra-Rojas et al, 2014), integration with crew scheduling (Huisman et al, 2005;Shen and Ni, 2006;Shen and Xia, 2009;Shen and Zhao, 2009;Steinzen et al, 2010), and integration with crew scheduling and rostering (Mesquita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Huisman et al (2004) proposed a dynamic vehicle scheduling approach to solve a sequence of rescheduling problems in real time, in which the disturbances affecting the trip times are considered. Moreover, a review on more schedule recovery methods can be found in Visentini et al (2014).…”
Section: Introductionmentioning
confidence: 99%